2022
DOI: 10.1093/nargab/lqac057
|View full text |Cite
|
Sign up to set email alerts
|

Mining bacterial NGS data vastly expands the complete genomes of temperate phages

Abstract: Temperate phages (active prophages induced from bacteria) help control pathogenicity, modulate community structure, and maintain gut homeostasis. Complete phage genome sequences are indispensable for understanding phage biology. Traditional plaque techniques are inapplicable to temperate phages due to their lysogenicity, curbing their identification and characterization. Existing bioinformatics tools for prophage prediction usually fail to detect accurate and complete temperate phage genomes. This study propos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
(99 reference statements)
0
14
0
Order By: Relevance
“…This study identified a total of 8,777 temperate phages specifically associated with S. enterica from the comprehensive public and compromised temperate phage database generated in our previous study ( Zhang et al, 2022 ). These temperate phages were detected from the bacterial next-generation sequencing data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identified a total of 8,777 temperate phages specifically associated with S. enterica from the comprehensive public and compromised temperate phage database generated in our previous study ( Zhang et al, 2022 ). These temperate phages were detected from the bacterial next-generation sequencing data.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we observed that the Salmonella enterica genome contains the largest number of temperate phages compared to other sequenced bacterial species ( Zhang et al, 2022 ). Salmonella enterica is a zoonotic pathogen of substantial concern to global human and animal health ( Knodler and Elfenbein, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, temperate phage and prophage sequences were also screened for ARGs. A total of 66,823 temperate phage sequences were identified using the TemPhD [38] method (fetched from the PhageScope database [39]) and 49,254 prophage sequences extracted from the PhageClouds database [40] (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, temperate phage and prophage sequences were also screened for ARGs. A total of 66,823 temperate phage sequences were identified using the TemPhD [38] method (fetched from the PhageScope database [39]) and 49,254 prophage sequences extracted from the PhageClouds database [40] (Figure 1C). Interestingly, a maximum fraction of ARG-carrying phages were found in temperate and prophages sequences, 2.15% and 0.66%, in TemPhD and Phagecloud datasets, respectively, and the least occurrence was found in the MGV environmental database.…”
Section: Presence Of Args In Phage Genomesmentioning
confidence: 99%
“…Additionally, the categorization of viral taxonomy is still a topic of discussion (Walker et al, 2022). Though there have been recent efforts to expand databases (Camargo et al, 2023; Zhang et al, 2022), the overall understanding of viral diversity is still not complete (Yan et al, 2023). We have assembled a unique phage sequence database using recently published genomic data.…”
Section: Methodsmentioning
confidence: 99%